2023
DOI: 10.3390/s23052614
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Scintillating Fiber Dosimeter for Radiation Dose Quality Control in Computed Tomography

Abstract: (1) Background: The IVIscan is a commercially available scintillating fiber detector designed for quality assurance and in vivo dosimetry in computed tomography (CT). In this work, we investigated the performance of the IVIscan scintillator and associated method in a wide range of beam width from three CT manufacturers and compared it to a CT chamber designed for Computed Tomography Dose Index (CTDI) measurements. (2) Methods: We measured weighted CTDI (CTDIw) with each detector in accordance with the requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Specifically, the relative differences were <5% when changing the IPS from 3 to 15 or the mA from 20 to 60 or 100. As expected, because of previous studies on scintillating fiber dosimeters [ 24 ], when dropping the tube voltage from 125 to 100 kV, the relative dose difference was −8.7%. Notably, when varying the field size, the maximum relative dose difference was −7.2%, which occurred at a field size of 2 cm.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, the relative differences were <5% when changing the IPS from 3 to 15 or the mA from 20 to 60 or 100. As expected, because of previous studies on scintillating fiber dosimeters [ 24 ], when dropping the tube voltage from 125 to 100 kV, the relative dose difference was −8.7%. Notably, when varying the field size, the maximum relative dose difference was −7.2%, which occurred at a field size of 2 cm.…”
Section: Discussionsupporting
confidence: 87%
“…During this study, we cross-calibrated the IVI-CBCT dosimeter with a pencil chamber that had itself been calibrated in a primary standards laboratory. To test the accuracy with which the device measured CTDI, we repeated this cross-calibration for three acquisition CBCT protocols (Pelvis, Pelvis Large, and Spotlight) that require different kV adjustments (125 or 140 kV) and fans (half fan or full fan); these protocols were chosen because our previous evaluations of the detector with CT scanners showed a non-negligible dependence of the response of the fiber on the energy of the beam; specifically, we found up to 31% of dose deviations between a scintillating fiber dosimeter and a pencil ionization chamber in a previous study [ 24 ]. Thus, we acquired 10 measurements for each detector and each protocol and found that IVI-CBCT demonstrated better constancy (coefficient of variation ranged from 0.1% to 0.5%) than the pencil chamber (0.5% to 1.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation